Answer:
2 (x^3 - x^2 + 2 x + 1)
Explanation:
Simplify the following:
-(2 x^2 - 3 x^3 + 1) - x^3 + 4 x + 3
Factor -1 out of -3 x^3 + 2 x^2 + 1:
--(3 x^3 - 2 x^2 - 1) - x^3 + 4 x + 3
(-1)^2 = 1:
3 x^3 - 2 x^2 - 1 - x^3 + 4 x + 3
Grouping like terms, 3 x^3 - x^3 - 2 x^2 + 4 x - 1 + 3 = (-x^3 + 3 x^3) - 2 x^2 + 4 x + (3 - 1):
(-x^3 + 3 x^3) - 2 x^2 + 4 x + (3 - 1)
3 x^3 - x^3 = 2 x^3:
2 x^3 - 2 x^2 + 4 x + (3 - 1)
3 - 1 = 2:
2 x^3 - 2 x^2 + 4 x + 2
Factor 2 out of 2 x^3 - 2 x^2 + 4 x + 2:
Answer: 2 (x^3 - x^2 + 2 x + 1)